2002
DOI: 10.1021/ie0103207
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Zinc(II) from Spent Hydrochloric Acid Solutions from Zinc Hot Galvanizing Plants

Abstract: The extraction of zinc(II) from spent pickling hydrochloric acid solutions obtained in zinc hot-dip galvanizing plants was studied. Tributyl phosphate and its mixtures with di(2-ethylhexyl)phosphoric acid (DEHPA), HOE F 2562, ALIQUAT 336, ALAMINE 304, ALAMINE 308, ALAMINE 310, ALAMINE 336, and CYANEX 301 were used as extractants. The acidic extractants (CYANEX 301 and DEHPA) did not extract both zinc(II) and iron(III) from 10% HCl. Precipitation occurred or stable emulsions were formed when ALAMINE 304, ALAMIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…The author's research group has been working on selective zinc recovery from hydrochloric acid SPS for a couple of years applying not only diffusion dialysis and retardation but also classical [59][60][61][62][63][64][65][66] and membrane based [64,[67][68][69] solvent extraction (see Table 5). …”
Section: Classical and Membrane Based Solvent Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The author's research group has been working on selective zinc recovery from hydrochloric acid SPS for a couple of years applying not only diffusion dialysis and retardation but also classical [59][60][61][62][63][64][65][66] and membrane based [64,[67][68][69] solvent extraction (see Table 5). …”
Section: Classical and Membrane Based Solvent Extractionmentioning
confidence: 99%
“…After screening for the most suitable extractant from among a wide spectrum of compounds (Table 5), TBP (E Zn(II) ∼100%) and dibutyl(butyl) phosphonate (DBBP; E Zn(II) ∼80%) have been selected for further examination [59,61,64,70]. The criteria of extractant suitability for SPS regeneration confirmed by Australian researchers [71] are as follows: good phase disengagement after extraction and stripping, high selectivity of zinc extraction over iron(II) and easy zinc stripping with water.…”
Section: Classical and Membrane Based Solvent Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies are reported on Alamine 308 as extractant for acids and transition metals [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…1 that iron(II) exists exclusively as FeCl + while zinc occurs as neutral ZnCl 2 in both effluents. According to Regel et al [26] and Cierpiszewski et al [27] who used the program Medusa to roughly estimate the distribution of various chlorocomplexes in spent HCl pickling liquors, iron(II) may also exists as Fe 2+ additionally to FeCl + while zinc exists almost completely in the anionic forms as ZnCl 4 2− and ZnCl 3 − . Both analysis are theoretical and dependent on the species considered to exist in the aqueous system (and their respective concentrations as well), and also the stability constants used in the calculations.…”
Section: Characterization Of Effluent Streams Produced By the Zinc-plmentioning
confidence: 99%